Waste-to-energy: Dehalogenation of plastic-containing wastes. (March 2016) - Shen, Yafei; Zhao, Rong; Wang, Junfeng; Chen, Xingming; Ge, Xinlei; Chen, Mindong
Abstract : Graphical abstract: Highlights: Dehalogenation of plastic wastes with biomasses for clean energy is reviewed. Mechanochemical or hydrothermal pre-treatment with biomasses can enhance the dehalogenation of waste plastics. The solid fuel properties (e.g., particle size) can be improved by co-HTT with biomass. Halogenated compounds from downstream thermal decomposition were eliminated using catalysts and sorbents. Dehalogenation of plastic wastes initially focus on the transformation of organic to inorganic halogen. Abstract: The dehalogenation measurements could be carried out with the decomposition of plastic wastes simultaneously or successively. This paper reviewed the progresses in dehalogenation followed by thermochemical conversion of plastic-containing wastes for clean energy production. The pre-treatment method of MCT or HTT can eliminate the halogen in plastic wastes. The additives such as alkali-based metal oxides (e.g., CaO, NaOH), iron powders and minerals (e.g., quartz) can work as reaction mediums and accelerators with the objective of enhancing the mechanochemical reaction. The dehalogenation of waste plastics could be achieved by co-grinding with sustainable additives such as bio-wastes (e.g., rice husk), recyclable minerals (e.g., red mud) via MCT for solid fuels production. Interestingly, the solid fuel properties (e.g., particle size) could be significantly improved by HTT in addition with lignocellulosic biomass. Furthermore, the halogenated compounds in downstream thermal process could be eliminated by using catalysts and adsorbents. Most dehalogenation of plastic wastes primarily focuses on the transformation of organic halogen into inorganic halogen in terms of halogen hydrides or salts. The integrated process of MCT or HTT with the catalytic thermal decomposition is a promising way for clean energy production. The low-cost additives (e.g., red mud) used in the pre-treatment by MCT or HTT lead to a considerable synergistic effects including catalytic effect contributing to the follow-up thermal decomposition.